Terapia fonoaudiológica assistida por animais: proposta de tratamento para sujeitos que gaguejam - Ichitani, Tatiane (2020)
(ESTUDO 1) - Effects of proposed speech therapy associated with animal assisted therapy on the treatment of persons who stutter. INTRODUCTION: Animal Assisted Intervention (IAA) is an approach that incorporate animals in the areas of health, education, and social service, with an aim to obtain therapeutic benefits. While there has been research on the subject with relevant results in various areas of health and education, there are still few studies inherent to speech therapy. In Brazil, some studies show that IAA favors communicative intent in the elderly and improves symptoms of oral and written language disorders in children. In this context, this study investigates the effects of the Animal Assisted Therapy (TAA) modality, specifically in participants who stutter. In order to seek scientific evidence that justifies a therapeutic proposal built on these interfaces for the care of this population, the hypothesis of the study is that the dog's relationship with the subject enables a context of depathologization that favors fluency. OBJECTIVE: To evaluate the effects of proposed speech therapy associated with animal assisted therapy in the treatment of participants who stutter. METHOD: This is a qualitative intervention research. Two Golden Retrievers, who were co-therapist dogs, were selected and trained for the function. The sample included 8 participants, adolescents and adults, of both sexes, diagnosed with developmental stuttering; these were divided into two groups. In the Control Group (CG), the participants underwent speech therapy without a dog; in the Intervention Group (IG), the participants were administered TAA. Procedure: Pre and post-treatment evaluation was performed where the creep indicators were analyzed. Qualitative data were also analyzed. RESULTS: There was no statistically significant difference between the groups. Qualitative data indicated some differences, such as greater motivation and more commitment in IG, enabling symbolic elaboration of psychic contents. CONCLUSION: The presence of a dog facilitates affective exchanges, a welcoming feeling, body relaxation, and helps develop a patient-therapist bond and in the symbolic elaboration of psychic contents. (ESTUDO 2) - Effects of the Presence of a Dog on the Psychic Content Expression of a Stuttering Person: Case Report. INTRODUCTION: Stuttering has negative impacts on an individual’s quality of life and is associated with a higher risk of the development of social and psychological problems. From this perspective, despite the diversity of the etiological hypotheses for and treatments of stuttering, the interface between psychology and speech therapy in the approach to the biopsychic aspects involved in this clinical scenario stands out. Recent research indicates that the presence (specifically of dogs) can assist patients in the symbolic elaboration of psychic content. OBJECTIVE: Evaluate the effects of a dog's presence on the expression of the psychic content of a stuttering person, with the hypothesis that framing may reduce symptoms. CASE PRESENTATION: The subject is M., female, 45 years old, married, without children, a hairdressing assistant, with elementary school completed. She underwent the process of speech therapy in the presence of a dog. A semidirected interview was conducted after this process. A co-therapist dog of the Golden Retriever breed participated in all sessions. RESULTS AND DISCUSSION: The relevant subjective content observed in the setting during the speech therapy process, which seems to have been mobilized by the framework established by the interaction among the therapist, the patient, and the dog, seems to demonstrate an association with the manifestation of disfluencies. The dog made physical contact with, supported, motivated and welcomed the subject in situations in which psychic conflicts were demonstrated. CONCLUSION: This clinical case study indicates that the dog's presence and interaction framework favored the reduction of stuttering symptoms, promoting a welcoming environment that enabled the subject's psyche-soma integration